The duchess : a novel - Steel, Danielle (New York : Random House Large Print Publishing, 2017)
Turned out of her ancestral home by her half-brothers after the death of their father, Angelique Latham moves to Paris and opens an elegant brothel with her inheritance.
Keywords: Aristocracy (Social class) -- Fiction; Brothels -- Fiction; Paris (France) -- History -- 19th century -- Fiction